The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1039/d1dt03737d
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fe-clustering on the water oxidation performance of two-dimensional layered double hydroxides

Abstract: Among the two-dimensional (2D) materials family, layered double hydroxides (LDHs) represent a key member due to their unparalleled chemical versatility. Specially, those Fe-based LDHs are distinguished candidates considering their high...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…Once the LH phases have been structurally and electronically characterized, we proceed with the analysis of their electrochemical performance in terms of the OER by measuring the water oxidation in a three-electrode cell in alkaline media (1 M KOH aqueous solution). For the sake of clarity, glassy carbon has been employed to avoid hidden catalyst–electrode interactions …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Once the LH phases have been structurally and electronically characterized, we proceed with the analysis of their electrochemical performance in terms of the OER by measuring the water oxidation in a three-electrode cell in alkaline media (1 M KOH aqueous solution). For the sake of clarity, glassy carbon has been employed to avoid hidden catalyst–electrode interactions …”
Section: Resultsmentioning
confidence: 99%
“…For the sake of clarity, glassy carbon has been employed to avoid hidden catalyst−electrode interactions. 13 As a first step, cyclic voltammetry (CV) measurements were performed in order to drive the activation of the electroactive centers. As it is possible to observe in Figure 4, the peaks ascribable to the Co redox processes display a characteristic shape depending on their local environments (chemical identity), as well as a specific continuous increment during the successive cycles.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the structural and electronic description, we performed the electrochemical characterisation of all the samples under alkaline oxygen evolution reaction (OER) conditions, by employing a three‐electrode cell (glassy carbon electrode to avoid catalyst‐electrode transformation) [52] and using 1 M KOH solution with a purity of 99.98 % (Figure 4). Firstly, we proceeded by activating the electroactive material through 30 cyclic voltammetries at a scan rate of 50 mV/s.…”
Section: Resultsmentioning
confidence: 99%
“…[17][18][19] Hence, numerous strategies have been developed to further optimize the electrocatalytic performance of NiFe-LDH, including morphology modulation, anion exchange or intercalation, heteroatom doping or substitution, and defect engineering. [20][21][22][23][24][25] Liu et al synthesized oxygen vacancy-rich hierarchical NiFe-LDH microtubes assembled using twodimensional nanosheets via a template-assisted strategy as a way to increase the number of catalytically active sites. 26 Wu et al reported a surface strategy to manipulate the coordina-tively unsaturated metal sites of NiFe-LDH to enhance the OER activity of the catalyst by using an optimized amount of ammonium fluoride (NH 4 F) as a metal-complexing agent.…”
Section: Introductionmentioning
confidence: 99%